Extraction induced by emulsion breaking as a tool for simultaneous multi-element determination in used lubricating oils by ICP-MS. Issue 11 (7th June 2015) - He, Yang-Ming; Zhao, Fang-Fang; Zhou, Ying; Ahmad, Farooq; Ling, Zhao-Xing
<x xml:space="preserve">Abstract</x> A novel method was developed for determination of metals in lubricating oils by ICP-MS based on extraction induced by emulsion breaking.